2019
DOI: 10.1038/s41598-019-46224-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxicity and antifungal properties of copper(II) and cobalt(II) complexes with imidazole-4-acetate anion or 1-allylimidazole

Abstract: The physicochemical properties of metal complexes determine their potential applications as antitumor agents. In this study, the antitumor properties of mononuclear cobalt(II) and copper(II) coordination compounds (stoichiometry: [Co(iaa) 2 (H 2 O) 2 ]·H 2 O (iaa = imidazole-4-acetate anion), [Co(1-allim) 6 ](NO 3 ) 2 (1-allim = 1-allylimidazole), [Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…The in vitro tests showed that cobalt(III) complexes (43, Figure 9) were more active against Gram-positive bacteria (e.g., S. aureus) and fungal strains (C. albicans) with MIC values of 0.7-3 and 7-250 µg/mL, respectively, and less active against Gram-negative strains, such as E. coli and K. pneumoniae. Several other types of cobalt metal complexes have been tested for their antimicrobial efficacy, however, their activities were not found remarkably high [111][112][113][114][115][116][117][118][119][120][121].…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…The in vitro tests showed that cobalt(III) complexes (43, Figure 9) were more active against Gram-positive bacteria (e.g., S. aureus) and fungal strains (C. albicans) with MIC values of 0.7-3 and 7-250 µg/mL, respectively, and less active against Gram-negative strains, such as E. coli and K. pneumoniae. Several other types of cobalt metal complexes have been tested for their antimicrobial efficacy, however, their activities were not found remarkably high [111][112][113][114][115][116][117][118][119][120][121].…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…reported a series of copper(II) and cobalt(II) complexes with the ligands imidazole‐4‐acetate (iaa) and 1‐allylimidazole and found that the Co II ‐iaa compound ( Co2 ) showed a significant decrease (≈5 log) in colony forming units (CFU) against Candida albicans at 60 μM in vitro, while not displaying any cytotoxicity at the same concentration. Unfortunately no dose‐response or activity at lower concentrations were reported [14] . In 2019, Hashmi and co‐workers described the preparation of Co, Ni, Zn, and Cu complexes bearing a 1,10‐phenanthroline ligand as well as a Schiff‐base‐derived ligand with a pendent indole ring (e.g., Ni1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately no dose-response or activity at lower concentrations were reported. [14] In 2019, Hashmi and co-workers described the preparation of Co, Ni, Zn, and Cu complexesb earing a1 ,10-phenanthroline ligand as well as aS chiff-base-de-rived ligand with ap endent indole ring (e.g., Ni1). The cobalt and nickel complexes showed high antifungal activity against aseries of C. albicans strains (includings ome fluconazole-resistant isolates), with MICs ranging from 0.25-8 mgmL À1 .H owever, no studies against other fungal pathogens or cytotoxicity against human cell lines were reported.…”
Section: Introductionmentioning
confidence: 99%
“…This article presents the main mechanisms of the in vitro anticancer activity of metal complexes (apoptosis, autophagy, cell cycle inhibition, DNA damage) described in the literature to date. Studies on cell lines indicate that metal complexes, especially copper complexes, are selective for cancer cells [ 103 , 104 , 105 ]. Metal complexes might soon prove to be good alternatives to cisplatin, which is still the most popular, but with many side effects and fast emerging drug-resistance in cancer cells.…”
Section: Discussionmentioning
confidence: 99%